Contradictions and tensions in the employment of older persons in modern Russia - Sizova, Irina L.; Orlova, Natalia S. (Journal of the Belarusian State University. Sociology, 2021)
The article identifies the main contradictions and tensions in the work and employment of older people in the modern Russian economy. On the basis of current theoretical concepts and discussions, the definition of older workers is given and the key problems in their employment are identified on the basis of Federal State Statistic Servece and research results. The main contradictions are primarily related to doubts about the possibility of fully using the labour potential of older people in the modern economy and the recognition of the need for this. In addition, Russian society still continues to be dominated by stereotypes regarding older generations of workers and, in particular, the elderly. In the labour market, they are clearly manifested in the difficulties of employment after the age of 45 and in their segregation into the sector of low-paid and unattractive work. As the age increases, the position of a person in the labour market deteriorates, and the retirement age for many people who are still actually healthy and fully able-bodied becomes a marker of liberation from the compulsions and discrimination of the Russian labour and employment system. For the majority of people who retire, the main factor that keeps them at work is only income, which, in combination with a pension, allows them to lead a normal lifestyle. In this context, education focused on the needs of age-related workers is of particular importance. The situation is such that, on the one hand, it is necessary to implement programs of retraining and systematic professional development of employees at older ages, and, on the other hand, this goal is useless due to the lack of motivation on the part of the employees themselves.
Keywords: older workers; labour potential; retirement age; labour market; employment; pension reform; education and qualifications